An overview of Bacillus proteases: from production to application. (3rd April 2018) - Contesini, Fabiano Jares; Melo, Ricardo Rodrigues de; Sato, Hélia Harumi
Abstract: Proteases have a broad range of applications in industrial processes and products and are representative of most worldwide enzyme sales. The genus Bacillus is probably the most important bacterial source of proteases and is capable of producing high yields of neutral and alkaline proteolytic enzymes with remarkable properties, such as high stability towards extreme temperatures, pH, organic solvents, detergents and oxidizing compounds. Therefore, several strategies have been developed for the cost-effective production of Bacillus proteases, including optimization of the fermentation parameters. Moreover, there are many studies on the use of low-cost substrates for submerged and solid state fermentation. Other alternatives include genetic tools such as protein engineering in order to obtain more active and stable proteases and strain engineering to better secrete recombinant proteases from Bacillus through homologous and heterologous protein expression. There has been extensive research on proteases because of the broad number of applications for these enzymes, such as in detergent formulations for the removal of blood stains from fabrics, production of bioactive peptides, food processing, enantioselective reactions, and dehairing of skins. Moreover, many commercial proteases have been characterized and purified from different Bacillus species. Therefore, this review highlights the production, purification, characterization, and application of proteases from a number of Bacillus species.